Translation of Foreign Culturally Colourful Metaphors Into the Native Language (e-Journal of Linguistics, 2020)
Translation of culturally coloured words has long been in the focus oflinguists. This lexicon is also called by linguists as the words withoutlexical equivalents in other languages. The question is actual for itsimportance for translators, who face with frequent difficulties in theprocess of translation of the texts with culturally coloured lexicon.Interpretation of culturally coloured metaphors requires not only a closeacquaintance with the English culturally coloured words but also asufficient information about the phraseological system of the nativelanguage. The semantical equivalents of English metaphors can be foundin the native metaphorical system no matter in which lexical structuresthe identical or similar metaphorical meanings may find theirexpression. Possibility of finding the semantical equivalents of Englishmetaphors in the native language is conditioned with the commonthinking way of peoples speaking different languages who in their longlife experience have come across with the same situations allowing tocreate similar metaphorical expressions in different lexical ways.Study of language and culture in close ties was always in the focus oflinguists from the point of view of communication and translation fromone language into another. Scientists come to the conclusion that anylanguage has a special semantic field which creates a difficulty fortranslating from one language into another. Such a lexical layer reflectsjust the national background, ethic and aesthetic life of a concrete peopleformed during many years.
Keywords: culture; language; metaphor; equiavalent; translation; reality